غالب اور وحدت الوجود: The Almighty and the Oneness of Being - Baig, Dr. Muhammad Shahzad Akhtar (Zoraiz, 2025)
Ghalib’s religion or life philosophy is “Wahdat-ul-Wujood”, which he observed after cognition. This belief can be expressed shortly but the Ghalib has used mystical intuition, poetic imagination and logical reasoning to state it, is really unique and incomparable. This belief is a core section of Ghalib’s poetic wisdom (intellect). The freshness of personal disclosure distinguishes him from other poets. This concept has played a vital role in forming Ghalib’s religious consciousness. In this research paper, analytical study of Ghalib’s belief Wahdat-ul-Wujood has been presented.